Forecasting inflation in Brazil with machine learning methods : integrating shrinkage method for variable selection with Shapley value interpretation - Pereira, Felipe Gonçalves (2024)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2024.